Identification of Rare Variants in ATP8B4 as a Risk Factor for Systemic Sclerosis by Whole‐Exome Sequencing. Issue 1 (January 2016) - Gao, Li; Emond, Mary J.; Louie, Tin; Cheadle, Chris; Berger, Alan E.; Rafaels, Nicholas; Vergara, Candelaria; Kim, Yoonhee; Taub, Margaret A.; Ruczinski, Ingo; Mathai, Stephen C.; Rich, Stephen S.; et al.
Abstract : Objective: To determine the contribution of rare variants as genetic modifiers of the expressivity, penetrance, and severity of systemic sclerosis (SSc). Methods: We performed whole‐exome sequencing of 78 European American patients with SSc, including 35 patients without pulmonary arterial hypertension (PAH) and 43 patients with PAH. Association testing of case–control probability for rare variants was performed using the unified sequence kernel association test with optimal kernel weighting and small sample adjustment by comparing all SSc patients with a reference population of 3, 179 controls from the Exome Sequencing Project 5, 500 exome data set. Replication genotyping was performed in an independent sample of 3, 263 patients (415 patients with SSc and 2, 848 controls). We conducted expression profiling of messenger RNA from 61 SSc patients (19 without PAH and 42 with PAH) and 41 corresponding controls. Results: The ATP8B4 gene was associated with a significant increase in the risk of SSc ( P = 2.77 × 10 −7 ). Among the 64 ATP8B4 variants tested, a single missense variant, c.1308C>G (F436L, rs55687265), provided the most compelling evidence of association ( P = 9.35 × 10 −10, odds ratio [OR] 6.11), which was confirmed in the replication cohort ( P = 0.012, OR 1.86) and meta‐analysis ( P = 1.92 × 10 −7, OR 2.5). Genes involved in E3 ubiquitin‐protein ligase complex ( ASB10 ) and cyclic nucleotide gated channelopathies ( CNGB3 ) as well as HLA–DRB5 and HSPB2 (heat‐shock protein 27) provided additional evidence of association ( P < 10 −5 ). Differential ATP8B4 expression was observed among the SSc patients compared to the controls ( P = 0.0005). Conclusion: ATP8B4 may represent a putative genetic risk factor for SSc and pulmonary vascular complications.